1981
DOI: 10.1016/0005-2736(81)90265-0
|View full text |Cite
|
Sign up to set email alerts
|

Membrane fusion of secretory vesicles and liposomes Two different types of fusion

Abstract: Secretory vesieles isolated from adrenal medulla were found to fuse in vitro in response to incubation with Ca 2 +. Intervesicular fusion was detected by electron microscopy and was indicated by the appearance of twinned vesieies in freeze-fractured suspensions of vesieles and in thin-sectioned pellet. Two types of fusion could be distinguished: Type I, occurring between 10-7 M and 10-4 M Ca 2 +, was specific for ea 2 +, was inhibited by other divalent cations and was abolished by pretreatment of vesieles with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

1982
1982
1995
1995

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(18 citation statements)
references
References 60 publications
(58 reference statements)
2
16
0
Order By: Relevance
“…Therefore, the granules seen in the present study were probably not vacuoles but chromaffin granules. Fusion of several chromaffin granules at high Ca 21 concentration (about 1 1tM) has been reported in in vitro studies (20,21). These large chromaffin granules, observed in the present study, may be produced by a …”
Section: Discussionmentioning
confidence: 75%
“…Therefore, the granules seen in the present study were probably not vacuoles but chromaffin granules. Fusion of several chromaffin granules at high Ca 21 concentration (about 1 1tM) has been reported in in vitro studies (20,21). These large chromaffin granules, observed in the present study, may be produced by a …”
Section: Discussionmentioning
confidence: 75%
“…An inherent puzzle, which is not yet solved, is that secretory vesicles fuse upon addition of Ca2+ [2] and that the same organelles are, in addition, able to take up Ca2+ . That means the same membrane, within the sequence of events between stimulus and secretion by exocytosis, acts as an acceptor of the signal as weIl as a 'scavenger' of the signal.…”
Section: Discussionmentioning
confidence: 99%
“…In earlier work [2] high affinity-binding sites for Ca2+ have been identified on the secretory vesicle membrane. Occupation of these sites has been found to parallel the fusion of secretory vesicles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that mitochondria are the site of accumulation of calcium (30,32), and that A23187 induces the calcium release from the intracellular stores (38). Kurihara and Fujita (29)) have reported that calcium ions necessary for exocytosis and membrane fusion (8,12,18,37) are derived not only from the extracellular fluid but also from the mitochondrial matrix. Moreover several workers (28, 33-35, 47, 51-53) have noticed Ca2+-ATPase activity in the mitochondria of different types of secretory cells and they proposed that mitochondria are exclusively concerned with the Ca2+ accumulation and that Ca2+-ATPase activity in mitochondria may help to decrease intracellular Ca2-concentrations in cells.…”
Section: Discussionmentioning
confidence: 99%